ENHANCED PERFORMANCE OF DYE-SENSITIZED SOLAR CELLS USING MELINJO PEEL (GNETUM GNEMON) DYE AS SENSITIZER - Hardani Hardani; Lily Maysari Angraini (Universitas Mataram, 2019)
It has been successfully identified and characterized by dye Melinjo peel (Gnetum gnemon) as an active material for Dye Sensitized Solar Cells (DSSC). The sample is formed in the structure of a working pair of electrode sandwiches and opposing electrodes. The dye extraction process (Dye) of the melinjo was stirred for 1 hour and then left to stand for 24 hours but there were only differences in how to doping dye into TiO2.Dye-sensitized solar cell (DSSC) is one of the photochemical electrical cells consisting of a photoelectrode, dye, electrolyte, and counter electrode. The purpose of using dyes in the DSSC is to extend the absorption spectrum to visible light because visible light has about 96% energy from sunlight. This article presents some experimental data on the nature of absorbance and the conductivity of natural dyes extracted from the plant as an application in the DSSC. Absorbance test using Spectrophotometer UV Visible 1601 PC and electrical properties test using Elkahfi 100 / Meter I-V. DSSC fabrication has been done using dye extract of melinjo (Gnetum gnemon) with a variety of immersion technique of drops and soak. The results show that natural dyes from natural material extraction have an absorbance spectrum of 380-520 nm range and the greatest conductivity is owned by melinjo (Gnetum gnemon). From the results of the test using AM Simulator 1.5G (100 mW / cm2) diesel simulator, it was found that the volume of TiO2 precursors affected the performance of DSSC solar cells and the overall conversion efficiency was 0.03% for the melinjo (Gnetum gnemon) dye by drops technique and 0.009% for the melinjo (Gnetum gnemon) dye by soak technique.